(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
In this paper, we introduce the concepts of fuzzy order convergence of double sequence, also define a new type of convergence, that is, Convergence and Cauchy of double sequence in fuzzy Riesz space and then prove some interesting results related to these notions.